WEBGIS-BASED GEOGRAPHICAL INFORMATION SYSTEM FOR MAPPING BAKERY SHOPS IN KISARAN CITY - Apridonal M, Yori; Mardalius; Bela Astuti (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Bakery MSMEs in Kisaran City play a significant role in the local economy, but their distribution data is still managed manually, making it difficult to access and analyze. This study aims to develop a WebGIS-based Geographic Information System to map and manage bakery MSME data digitally and in an integrated manner. The research methods include field surveys, spatial and non-spatial data collection, system design using UML, development with Leaflet.js and MySQL, and testing using the blackbox method. The results show that the resulting system is capable of displaying interactive maps with location details, business information, and an easy-to-use search feature. This system makes it easier for the government, business actors, and the public to access MSME information and supports data-based economic development planning. With the output in the form of publications in accredited journals, this research is expected to be an effective solution for MSME data management in other regions. Keyword: bakery; mapping; MSME; WebGIS Abstrak: UMKM toko roti di Kota Kisaran memiliki peran penting dalam perekonomian lokal, namun data persebarannya masih dikelola secara manual sehingga sulit diakses dan dianalisis. Penelitian ini bertujuan mengembangkan Sistem Informasi Geografis berbasis WebGIS untuk memetakan dan mengelola data UMKM toko roti secara digital dan terintegrasi. Metode penelitian meliputi survei lapangan, pengumpulan data spasial dan non-spasial, perancangan sistem menggunakan UML, pengembangan dengan Leaflet.js dan MySQL, serta pengujian menggunakan metode blackbox. Hasil penelitian menunjukkan sistem yang dihasilkan mampu menampilkan peta interaktif dengan detail lokasi, informasi usaha, dan fitur pencarian yang mudah digunakan. Sistem ini mempermudah pemerintah, pelaku usaha, dan masyarakat dalam mengakses informasi UMKM, serta mendukung perencanaan pembangunan ekonomi berbasis data. Dengan luaran berupa publikasi pada jurnal terakreditasi, penelitian ini diharapkan menjadi solusi efektif untuk pengelolaan data UMKM di daerah lain. Kata kunci; pemetaan; toko roti; UMKM; WebGIS